Faktor-Faktor yang Berpengaruh terhadap Nilai Perusahaan pada Perusahaan Manufaktur Sektor Industri Barang Konsumsi Periode 2018-2021 - Muhammad Fajar Rizqi Widyo Utomo; Batara Daniel Bagana (Ekonomis: Journal of Economics and Business, 2023)
This study aims to analyze and examine the factors that influence firm value. The variables used are company growth, profitability and capital structure. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the IDX in 2018-2021. The method used in data collection is purposive sampling. The number of samples used were 31 companies and the amount of data used was 124 data. When processing data, there are several company data that must be outliers. After outliers were made, the total sample obtained became 98 data. The analytical method used in this study is the quantitative analysis method. The results showed that the company's growth has no effect on firm value. Profitability has a positive effect on firm value. Capital structure has no effect on firm value.